Synthesis and Characterization of Copper Impregnated Mesoporous Carbon as Heterogeneous Catalyst for Phenylacetylene Carboxylation with Carbon Dioxide - Putri Nurul Amalia; Iman Abdullah; Dyah Utami Cahyaning Rahayu; Yuni Krisyuningsih Krisnandi (Indonesian Journal of Chemistry, 2021)
Carbon dioxide (CO2) is a compound that can potentially be used as a carbon source in the synthesis of fine chemicals. However, the utilization of CO2 is still constrained due to its inert and stable nature. Therefore, the presence of a catalyst is needed in CO2 conversion. This study aims to synthesize copper impregnated mesoporous carbon (Cu/MC) as a catalyst for phenylacetylene carboxylation reaction with CO2 to produce phenylpropiolic acid. The synthesis of mesoporous carbon was performed via the soft template method. The as-synthesized Cu/MC material was characterized by FTIR, SAA, XRD, and SEM-EDX. BET surface area analysis of mesoporous carbon showed that the material has a high surface area of 405.8 m2/g with an average pore diameter of 7.2 nm. XRD pattern of Cu/MC indicates that Cu has been successfully impregnated in the form of Cu(0) and Cu(I). Phenylacetylene carboxylation reaction with CO2 was carried out by varying reaction temperatures (25, 50, and 75 °C), amount of catalyst (28.6, 57.2, and 85.8 mg), type of base (Cs2CO3, K2CO3, and Na2CO3), and variation of support. The reaction mixtures were analyzed by HPLC and showed that the highest phenylacetylene conversion of 41% was obtained for the reaction at 75 °C using Cs2CO3 as a base.